2018
DOI: 10.18203/2394-6040.ijcmph20182646
|View full text |Cite
|
Sign up to set email alerts
|

Compliance of post exposure rabies vaccination among patients attending anti-rabies OPD in the Government Medical College, Nagpur

Abstract: Background: Rabies is a zoonotic disease, caused by the rabies virus, of the Lyssavirus genus, within the family Rhabdoviridae. The study was designed with the objective to assess the compliance of post exposure rabies vaccination among patients attending anti-rabies OPD in the government medical college, Nagpur.Methods: The study was retrospective record based study conducted from 1st July 2016 to 30th June 2017. The data was collected from the anti-rabies vaccination OPD register and analysed.Results: In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…In this study, cases of animal bites were more in males than females, similar to findings of Sharma et al 7 We also found that the majority of patients that is 89% were exposed to dog bites, similar to the findings of Karmakar et al and Nishant et al but more than findings by Gadapani et al [8][9][10] In our study, lower limb was the most commonly injured site in 59.3% patients and similar findings were observed in a study conducted by Domple et al 11 In the present study, 45 (15.7%) patients did not wash wound after bite as compared to study by Kawale et al where 3206 (53%) did not manage their wound. 12 In our study, it was seen that 78% of patients completed all doses of ARV which was similar to findings of Lilare et al and Jena et al 6,13 The compliance to ARV in our study was more than findings by Nishant et al , Titoria et al and Praveen et al 9,14,15 Compliance to RIG in our study was 63.3% which is in accordance with findings by Kawale et al and Datta et al 12,16 There was significant association between compliance to ARV last dose with the type of animal. Similar results were found in a study conducted by Shivasakthimani et al and Wadde et al 17,18 There was significant association found between compliance to RIG with gender, socioeconomic status, type of animal and type of wound.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, cases of animal bites were more in males than females, similar to findings of Sharma et al 7 We also found that the majority of patients that is 89% were exposed to dog bites, similar to the findings of Karmakar et al and Nishant et al but more than findings by Gadapani et al [8][9][10] In our study, lower limb was the most commonly injured site in 59.3% patients and similar findings were observed in a study conducted by Domple et al 11 In the present study, 45 (15.7%) patients did not wash wound after bite as compared to study by Kawale et al where 3206 (53%) did not manage their wound. 12 In our study, it was seen that 78% of patients completed all doses of ARV which was similar to findings of Lilare et al and Jena et al 6,13 The compliance to ARV in our study was more than findings by Nishant et al , Titoria et al and Praveen et al 9,14,15 Compliance to RIG in our study was 63.3% which is in accordance with findings by Kawale et al and Datta et al 12,16 There was significant association between compliance to ARV last dose with the type of animal. Similar results were found in a study conducted by Shivasakthimani et al and Wadde et al 17,18 There was significant association found between compliance to RIG with gender, socioeconomic status, type of animal and type of wound.…”
Section: Discussionsupporting
confidence: 89%
“…From a study conducted by Lilare et al taken as reference, taking prevalence of 73.5% with 5% absolute error, the sample size estimated was 299. 6 The final sample size was rounded off to 300. Data collected was entered in MS Excel Sheet and analyzed using SPSS software Version 20.…”
Section: Sample Size Estimationmentioning
confidence: 99%
“…[ 10 ] and Lilare et al . [ 6 ] in their study reported that 64% and 72.2% of animal bite victims had washed the wound site, respectively. However, the findings of the present study were different from those reported by Jain et al .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, taking the population proportion (prevalence) for wound washing by the study participants following animal bite as 72.2% as per a study carried out by Lilare et al . [ 6 ] among patients attending anti-rabies OPD at the Government Medical College, Nagpur, and absolute error as 5%, the sample size was calculated using the following formula:…”
Section: Methodsmentioning
confidence: 99%
“…[ 12 ] and Lilare et al . [ 13 ] reported in their studies that 64% and 72.2% of animal bite victims had washed the wound site, respectively. However, the findings of the present study were different from those reported by Jain et al .…”
Section: Discussionmentioning
confidence: 99%